SLC25A42‐associated mitochondrial encephalomyopathy: Report of additional founder cases and functional characterization of a novel deletion. Issue 1 (4th May 2021) - Aldosary, Mazhor; Baselm, Shahad; Abdulrahim, Maha; Almass, Rawan; Alsagob, Maysoon; AlMasseri, Zainab; Huma, Rozeena; AlQuait, Laila; Al‐Shidi, Tarfa; Al‐Obeid, Eman; AlBakheet, Albandary; Alahideb, Basma; et al.
Abstract: SLC25A42 is the main transporter of coenzyme A (CoA) into mitochondria. To date, 15 individuals have been reported to have one of two bi‐allelic homozygous missense variants in the SLC25A42 as the cause of mitochondrial encephalomyopathy, of which 14 of them were of Saudi origin and share the same founder variant, c.871A > G:p.Asn291Asp. The other subject was of German origin with a variant at canonical splice site, c.380 + 2 T > A. Here, we describe the clinical manifestations and the disease course in additional six Saudi patients from four unrelated consanguineous families. While five patients have the Saudi founder p.Asn291Asp variant, one subject has a novel deletion. Functional analyses on fibroblasts obtained from this patient revealed that the deletion causes significant decrease in mitochondrial oxygen consumption and ATP production compared to healthy individuals. Moreover, extracellular acidification rate revealed significantly reduced glycolysis, glycolytic capacity, and glycolytic reserve as compared to control individuals. There were no changes in the mitochondrial DNA (mtDNA) content of patient fibroblasts. Immunoblotting experiments revealed significantly diminished protein expression due to the deletion. In conclusion, we report additional patients with SLC25A42‐associated mitochondrial encephalomyopathy. Our study expands the molecular spectrum of this condition and provides further evidence of mitochondrial dysfunction as a central cause of pathology. We therefore propose that this disorder should be included in the differential diagnosis of any patient with an unexplained motor and speech delay, recurrent encephalopathy with metabolic acidosis, intermittent or persistent dystonia, lactic acidosis, basal ganglia lesions and, especially, of Arab ethnicity. Finally, deep brain stimulation should be considered in the management of patients with life altering dystonia.